2010
DOI: 10.1590/s0074-02762010000100001
|View full text |Cite
|
Sign up to set email alerts
|

Transmission blocking vaccines to control insect-borne diseases: a review

Abstract: Insect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…To this end, use has been made of experimental models that mimick the intestinal microenvironment of the host, such as cultures of intestinal epithelial cells, macrophages and dendritic cells 411, 415, 416. Our results showed that the initial ability to invade the intestinal cell is similar between EIEC and Shigella , but that the expression of virulence genes ( ipaABCD , icsA , icsB , virF , virB ), capacity to escape from the phagosome, intracellular proliferation and dissemination of EIEC, as well as the ability to cause cell damage during the infection, are much lower than with S. flexneri 411 .…”
Section: Enteroinvasive E Colimentioning
confidence: 99%
“…To this end, use has been made of experimental models that mimick the intestinal microenvironment of the host, such as cultures of intestinal epithelial cells, macrophages and dendritic cells 411, 415, 416. Our results showed that the initial ability to invade the intestinal cell is similar between EIEC and Shigella , but that the expression of virulence genes ( ipaABCD , icsA , icsB , virF , virB ), capacity to escape from the phagosome, intracellular proliferation and dissemination of EIEC, as well as the ability to cause cell damage during the infection, are much lower than with S. flexneri 411 .…”
Section: Enteroinvasive E Colimentioning
confidence: 99%
“…In malaria studies, transmission-blocking vaccines (TBVs) had been reported by several laboratories (66)(67)(68). Mosquito proteins related to virus infection were selected as immunogens and showed a role in blocking dengue virus infection.…”
Section: Fig 6 Anti-mosgctl-7 Serum Inhibits Jev Infection In Vivo Anmentioning
confidence: 99%
“…The emergence of insecticide resistance as well as the lack of other efficient insecticidal tools to control disease vectors imply that new methodologies need to be developed in order to reduce vector-borne disease transmission [1]. For this, the study of vector-pathogen interaction pinpointing factors underlying vector competence can reveal new molecular targets to be disrupted, preventing pathogen transmission [2], [3].…”
Section: Introductionmentioning
confidence: 99%